Face Authentication System for Kindergarten Attendance with Notification (FASKA) - Abdul Hamid, Mariam; Mohd Shariff, Muhammad Faris Hakimi; Rosli, Muhammad Irsyad Ilmi; Sa’dan, Muhammad Syazwan (Multidisciplinary Applied Research and Innovation, 2025)
This project aims to produce a smart face authentication system application that provides user information on kindergarten students such as their name, parent’s phone, and guardian’s name. This application will inform the user about the attendance of the student just by detecting his or her face and then it will be stored in the attendance system whose sign is present. The face authentication system attendance aimed to resolve the manual attendance taking methods. It streamlines the process and reduces the workload of Teacher. This attendance system can surely effectively solve the problem by speeding up the attendance of kindergarten students. The project is integrated with the machine learning technology which is android operating system, Firebase, ML Kit, and also face recognition. The methodology we have chosen is a waterfall methodology model. This waterfall model has 5 important phases: requirements, design, implementation, testing, and maintenance. The project management of our methodology that has been chosen will determine how our work is planned and completed. It is important to our project that aims to solving issues related to inefficient manual attendance methods. This application offers a simpler and more flexible approach to taking attendance. As summary, face authentication system for kindergarten attendance application can enhances the workflow and ensures the authenticity of the attendance system. Implementing this solution can eliminate the identified problems.